Pergeseran Entitas Kuliner Madura: Adaptasi Budaya, dan Tradisi Kuliner Lokal Menjadi Komersialisasi - Hetti Mulyaningsih; Bangun Sentosa Dwi Haryanto; Muhamad Chairul Basrun Umanailo; Bagus Irawan (Universitas Medan Area, 2023)
This research aims to describe the changes resulting from culinary modernization in Madura, encompassing the regions of Bangkalan, Sampang, Pamekasan, and Sumenep. The method used is descriptive qualitative research with four stages: pre-research, data collection, data analysis, and presentation of the analysis results. Research informants were selected based on information from various sources, with the criteria of at least two generations of selling traditional food and the establishment of food stalls or eateries. The findings of the research reveal the relationship between culinary as cultural heritage and socio-cultural adaptation through the phenomenological processes of acculturation and assimilation. The analysis shows a shift in culinary flavors by eliminating some fundamental principles in the dishes, altering culinary habits and traditions. For example, the rujak (fruit salad) has transformed from salty and spicy to sweet and spicy, even changing the color from red to black. The adaptation of sweetness in rujak is influenced by the migration of Javanese people to Madura, bringing Javanese sugar and black shrimp paste, which have affected the flavor and contributed to the changes. Furthermore, Tajin Sobik, which was previously only found during the Idul Fitri celebration, is now easily obtainable in shops and food stalls on regular days. This shift is influenced by commercial needs that seize the economic opportunities of tourism. These changes are also influenced by economic, cultural, political, and traditional factors inherent in culinary entities. Culinary practitioners in Madura, who should preserve the culture, become agents of culinary change and contribute to the transformation of flavors, culinary culture, and traditions in Madura.